Maid in Manhattan - Goldsmith-Thomas, Elaine; Schindler, Deborah; Schiff, Paul.; Wade, Kevin, 1954-; Wang, Wayne, 1949-; Lopez, Jennifer, 1970-; Fiennes, Ralph; Richardson, Natasha; Tucci, Stanley; Posey, Tyler Garcia, 1991-; Conroy, Frances; Eigeman, Christopher; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2003)
A struggling single mom takes a job as a chambermaid at a luxury hotel in New York. she meets and falls in love with a sauve and sophisticated heir to an American political dynasty, who mistakes her for a society woman. When her real identity is revealed, the reality about their seperate lives sets in.
Originally produced as a motion picture in 2002.
Also issued on VHS.
Special features: widescreen and full screen presentations; blooper reel; theatrical trailer.
Director of photography, Karl Walter Lindenlaub ; editor, Craig McKay ; original music, Alan Silvestri ; costume designer, Albert Wolsky ; production designer, Jane Musky.
Jennifer Lopez, Ralph Fiennes, Natasha Richardson, Stanley Tucci, Tyler Garcia Posey, Frances Conroy, Chris Eigeman, Amy Sedaris, Bob Hoskins.
MPAA rating: PG-13; for some language/sexual references.
Keywords: Hotel cleaning personnel -- Drama; Man-woman relationships -- Drama; Politicians -- New York (State) -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired